The Influence of Marketing Mix Implementation on Customer Satisfaction Mediated by Purchase Decision at Thrifting Sunriseoriginal in Palu City - fachruddin, Muhammad; Parani, Syamsul Bahri Dg.; Bachri, Syamsul; Auriza, Mohammad Zeylo (Universitas Muhammadiyah Pontianak, 2025)
This study aims to analyze the influence of the marketing mix on customer satisfaction with purchase decision as a mediating variable at Thrifting Sunriseoriginal in Palu City. The research used a quantitative approach with purposive sampling of 90 respondents who made at least two purchases. Data were analyzed using SmartPLS version 4.1. The results show that the marketing mix has a positive and significant effect on both purchase decisions and customer satisfaction. However, the indirect effect of the marketing mix on satisfaction through purchase decisions is not significant. The study highlights the importance of optimizing marketing mix strategies to enhance customer satisfaction.